Role of Diagnostic D&C and Histopathology of Endometrium in Perimenopausal Abnormal Uterine Bleeding - Roy, Moumita; Begum, Shamsunnahar; Ara, Begum Hosne (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
Background: Abnormal uterine bleeding is common and important problem in perimenopausal women which has diverse etiology. Among different diagnostic procedures, Dilatation and Curettage (D&C) with histopathology of endometrium has an important role in the detection of underlying cause in perspective of its availability, low cost, and high diagnostic yield. The objective of diagnostic curettage in perimenopausal women with abnormal uterine bleeding is to detect endometrial abnormality. Methods: It was a hospital based cross-sectional study among fifty patients of 45 to 60 years old with history of perimenopausal bleeding, attending the inpatient and outpatient department of Sir Salimullah Medical College and Mitford Hospital, Dhaka. The cases were selected according to inclusion and exclusion criteria. Routine investigations and pelvic ultrasonograpy were done. Endometrial biopsy were taken by Diagnostic D & C. Chi-square test was used as test of statistical significance. Statistical Package of Social Science Software (SPSS, version 16.0) was used for statistical analysis of data. Results: Common histopathological pattern identified were endometrial hyperplasia (32%), and polyp (24%). Proliferative endometrium was found in 16% cases, secretory endometrium in 12%, endometrial carcinoma in 6%, endometritis in 4 % and atrophic endometrium in 6% patients. Conclusion: Endometrial biopsy is an essential step for all cases of perimenopausal and postmenopausal abnormal uterine bleeding to rule out malignancy. Bangladesh J Obstet Gynaecol, 2020; Vol. 35(1): 7-14